Optimization problems and maintenance policy for a parallel computing system with dependent components - Wang, Junyuan; Wang, Lubing; Zhao, Xufeng; Miao, Zhouqian (Annals of operations research, 2025)
This paper proposes the generalized maintenance policies for a computing system when the copula functions model the interdependency. In this paper, the dependence between the components has been modeled by three copula functions. We deal with random maintenance policies for repairable parallel systems with n dependent or independent components. Firstly, we discuss the maintenance first and last policies for parallel systems composed of dependent components. We consider the random maintenance policy for parallel systems that are dependent and attempt to find the optimal maintenance time by considering the copula framework. The expected cost rate is considered as objective function to minimize. For each policy, the optimal maintenance time that minimizes the mean cost rate is analyzed and discussed numerically. And we study the effects of model parameters on the optimal maintenance policy and compare the copula. The findings of the paper extend the results in the literature from system with independent components to dependent components. Numerical results are presented for components lifetime follow Weilbull distribution. Therefore manager can use the results to formulate the optimal decision problem of their parallel systems with dependent components.